2013
DOI: 10.1111/j.1521-0391.2013.12060.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Diurnal Cortisol Secretion Affects Abstinence Induction during a Lead‐in Period of a Clinical Trial for Depressed Cocaine‐Dependent Patients

Abstract: Background and Objective Hypothesizing that stress dysregulation may worsen cocaine dependence, we investigated the effect of diurnal cortisol secretion profile, suppression of cortisol secretion, and total cortisol secretion on retention, abstinence-based voucher earnings, days of cravings, and mood status of participants at the end of a 2-week medication-free lead-in prior to randomization in a clinical trial of mirtazapine (60 mg vs. placebo) for depressed cocaine-dependent patients. Methods We measured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We observed these cortisol measurements were positively associated with craving levels and negatively with the age of onset of drug consumption. Some studies about this topic have revealed that a deviation of cortisol secretion away from the homeostatic diurnal pattern in cocaine-dependent subjects was associated with reduced success at achieving early abstinence [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. This finding suggests a feed-forward cascade of effects of drugs on stress biology [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed these cortisol measurements were positively associated with craving levels and negatively with the age of onset of drug consumption. Some studies about this topic have revealed that a deviation of cortisol secretion away from the homeostatic diurnal pattern in cocaine-dependent subjects was associated with reduced success at achieving early abstinence [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. This finding suggests a feed-forward cascade of effects of drugs on stress biology [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this, some studies have demonstrated the influence of parental history of substance abuse on the risk of early drug abuse in their offspring [ 63 , 64 ], and for instance, higher morning cortisol levels have been found among crack cocaine users with positive family history and lower treatment retention [ 44 ]. Indeed, activation of the HPA response may be an early dysregulation associated with excessive and early drug taking that ultimately sensitizes the extrahypothalamic CRH systems [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Restlessness and Agitation Questionnaire ( RAQ ; Wong & Leventhal, 2014) used in this study consisted of 19 items (e.g. “Feeling wound up” and “Having difficulty keeping still”).…”
Section: Methodsmentioning
confidence: 99%